Young fatherhood, masculinities, and structural factors in South Africa - Makusha, Tawanda (Frontiers in Sociology, 2024)
BackgroundThis paper explores the intricate interplay between young fatherhood, masculinities, and structural factors in South Africa. The country grapples with a complex web of social, economic, and cultural dynamics that shape the experiences of young men’s transition into fatherhood.MethodsThis qualitative study used snowball and purposive sampling techniques. In-depth interviews were undertaken with 24 young biological fathers aged between 18 and 24 years in an informal settlement in Durban (12) and a rural community in Pietermaritzburg (12), KwaZulu-Natal. Four focus-group discussions, in groups of four participants, were conducted with 16 of the participants who took part in the in-depth interviews. Data were analysed thematically on the local constructions of young fatherhood and masculinities and how both were associated with structural factors.Results and discussionYoung fatherhood in South Africa is associated with a number of structural vulnerabilities, such as living in communities with high alcohol and drug abuse, low educational attainment, inadequate access to healthcare, unemployment, poverty, and crime. These structural vulnerabilities, deeply entrenched in the country’s history and socioeconomic fabric, together with prevailing notions of masculinities, often rooted in hegemonic ideals of dominance and control, intersect with societal expectations of fatherhood, thereby shaping young men’s identities, roles, and responsibilities as fathers.ConclusionThe findings suggest young men’s involvement during the transition to fatherhood appears multi-determined. To effectively support young fathers and promote family well-being, it is imperative to address the root causes of structural inequalities, challenge rigid norms of masculinities, and foster inclusive policies and programmes that empower young men to embrace their roles as caregivers and agents of change within their families and communities.